Novel naturally occurring autoantibodies attenuate α‐synuclein pathology in a mouse model of Parkinson's disease. Issue 1 (16th November 2022) - Li, Yiming; Wang, Tao; Meng, Lanxia; Jin, Lei; Liu, Congcong; Liang, Yangqiu; Ren, Lin; Liu, Yang; Liu, Yanshuang; Liu, Shuang; Li, Tete; Liang, Yanqi; et al.
Abstract: Aims: Accumulation and propagation of pathological α‐synuclein (α‐Syn) are the major contributing factors to the pathogenesis of Parkinson's disease (PD). Therapy to halt the spreading of α‐Syn pathology needs to be established. Methods: After phage display and affinity maturation, human‐derived anti‐α‐Syn autoantibodies were selected and applied to biochemical, cellular and animal models of PD. Results: The novel naturally occurring anti‐α‐Syn autoantibodies (α‐Syn‐nAbs), P21 and P22, selectively bind α‐Syn preformed fibrils (PFFs), recognise Lewy bodies (LBs) and Lewy neurites (LNs) in human PD brains, block α‐Syn fibrillization and inhibit the seeding of α‐Syn PFFs. Moreover, systematic administration of P21 and P22 attenuates α‐Syn pathology, degeneration of the nigrostriatal pathway and motor deficits in mice injected with α‐Syn PFFs. Conclusions: P21 and P22 attenuate α‐synuclein pathology and are promising candidates for PD treatment. Abstract : P21 and P22 selectively bind α‐Syn PFFs and recognize LBs and LNs in human PD brains. P21 and P22 block α‐Syn fibrillization and inhibit the seeding of α‐Syn PFFs. Systematic administration of P21 and P22 attenuates α‐Syn pathology, degeneration of the nigrostriatal pathway, and motor deficits in a mouse model of PD.